When Words Fail: The Causes and Intervention Models for Student Public Speaking Fear - Pradana, Sandi; Hartiwi, Juni; Puspita, Emma; Alhummaira, Satwika (LinguaScopes: International Journal of Language Education, 2025)
Public speaking fear, or glossophobia, constitutes a significant and widespread barrier to communication competence and socioeconomic integration for adult English as an Additional Language (EAL) learners, intensified by the effects of Foreign Language Anxiety (FLA). This Systematic Literature Review (SLR) employed the PRISMA framework to synthesize empirical evidence published between 2015 and the present (36 studies) regarding the causes and interventions for this phenomenon. Findings confirm that anxiety is driven by the dynamic interaction of psychological factors (fear of negative evaluation, low self-efficacy) and linguistic factors (L2 proficiency deficits, accent anxiety). Intervention models based on Cognitive-Behavioral Therapy (CBT), particularly when combined with Virtual Reality (VR) exposure, demonstrated the highest efficacy in producing large and sustained reductions in anxiety. The results advocate for adopting multi-modal, integrated curricula that systematically address both psychological resilience and linguistic insecurity within a supportive, low-stakes learning environment.